Transformational Leadership Practices in Curriculum Implementation (Environmental Education) in Secondary Schools in Siaya County, Kenya - Okoth, Ursulla A. (European Scientific Journal, ESJ, 2018)
Leadership practices promote accomplishment of goals in organizations. This paper focuses on the application of transformational leadership practices: Idealized influence, Inspirational motivation, Intellectual stimulation and Individualized consideration in curriculum implementation, Environmental Education (EE). The sample consisted of 183 teachers randomly selected from 30 secondary schools in Siaya County. A questionnaire was used in a descriptive survey research. The findings using the selected indicators were that head teachers: strived towards the collective goal of fulfilling a vision and were positive role models; had trust of teachers’ ability; made decisions all the time; encouraged students to work hard; and organized meetings with other schools to achieve subject objectives.